In-situ measurement of viscoelastic properties of fresh cement paste by a microrheology analyzer. (January 2016) - Zhang, Yanrong; Kong, Xiangming; Gao, Liang; Lu, Zichen; Zhou, Shiming; Dong, Biqin; Xing, Feng
Abstract: A microrheology analyzer was adapted to in-situ follow the development of viscoelastic properties of fresh cement pastes (FCPs) for the first time. It enables a non-disturbing measurement on the FCPs through monitoring the mean square displacement of cement particles, which gives an insight into the elastic and viscous properties of materials from a microstructural point of view. Various parameters including elastic index, macroscopic viscosity index, storage modulus, loss modulus and Maxwell parameters were obtained to quantitatively analyze the viscoelastic properties of FCPs. Results indicate that these parameters show a progressive increase with time at first and then stay stable. The incorporation of superplasticizer significantly decreases these parameters and their growth rates. Moreover, superplasticizer could evidently weaken the elastic feature of the FCP due to its effects of improving the dispersion of cement grains and retarding cement hydration. The effects of superplasticizer are more pronounced at lower water to cement ratio.